2015
DOI: 10.1093/aje/kwv042
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Residential Proximity to Power Plants and Adverse Birth Outcomes

Abstract: Few studies have assessed the associations between residential proximity to power plants and adverse birth outcomes including preterm delivery (PTD), very preterm delivery (VPTD), and term low birth weight (LBW). We geocoded 423,719 singleton Florida births born from 2004 to 2005 and all active power plants and determined residential proximity to the nearest power plant for each birth. Prenatal exposure to particulate matter less than 2.5 µm in diameter for women living near different types of power plants was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 35 publications
1
32
0
1
Order By: Relevance
“…Many prior preterm birth studies have focused on trafficrelated air pollution or nonspecific particulate matter exposures (21,22,(51)(52)(53)(54)(55)(56), although some have evaluated sourcespecific emissions (11,22,54). Four studies estimated the relationship between living near power plants and adverse birth outcomes (5)(6)(7)(8). Among 400,000 births in Florida, Ha et al (6) reported a 2.2% increase in odds of preterm delivery for each 5 km closer to any power plant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many prior preterm birth studies have focused on trafficrelated air pollution or nonspecific particulate matter exposures (21,22,(51)(52)(53)(54)(55)(56), although some have evaluated sourcespecific emissions (11,22,54). Four studies estimated the relationship between living near power plants and adverse birth outcomes (5)(6)(7)(8). Among 400,000 births in Florida, Ha et al (6) reported a 2.2% increase in odds of preterm delivery for each 5 km closer to any power plant.…”
Section: Discussionmentioning
confidence: 99%
“…Coal electricity accounted for 51% of US electricity generation in 2001 and 42% in 2011, with more plant retirements likely in the future (2). Residential proximity to active oil and coal power plants may harm health (1,3,4), particularly of pregnant women and developing fetuses (5)(6)(7)(8). Therefore, power plant retirements may improve birth outcomes, including the proportion of preterm birth.…”
mentioning
confidence: 99%
“…Prior literature has assessed the association between power plant proximity and birth outcomes [ 5 , 6 , 36 , 37 ]. We extended this literature, finding an association between power plant retirements and increased fertility.…”
Section: Discussionmentioning
confidence: 99%
“…Residential proximity to power plants has been linked to health outcomes such as cardiovascular and respiratory disease [ 4 ] and adverse birth outcomes [ 5 , 6 ]. Coal and oil plants, especially older and less efficient ones, typically emit more pollution than those run on natural gas [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, an important evolution in this research is to examine sources and components of fractionated PM 2.5 . One study identified power plants as important sources of PM 2.5 exposure, and illustrated that proximity to these plants specifically was associated with increased risk of preterm delivery (138). Additionally, two studies examining compounds present in PM 2.5 fractions suggested that elemental carbon and SO 4 specifically were associated with increased risk of PTB (111, 119).…”
Section: Environmental Chemicals and Ptbmentioning
confidence: 99%